KEPEMIMPINAN DIGITAL 4.0: KAJIAN SISTEMATIS KONSEPTUALISASI DAN PRAKTIK DALAM PENDIDIKAN - Abdul Hasan Saragih; Abdul Hamid K; Sugiharto Sugiharto; Awal Kurnia Putra Nasution; Ricki Ananda; Oktaviana Bangun; Iqbal Kamil Siregar; Bachtiar Efendi; Rafika Sari Br Sembiring (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study presents a comprehensive analysis of the evolution of digital leadership in education, tracing its development from the initial concept of e-leadership to Leadership 4.0 amid the era of digital transformation and artificial intelligence (AI). "A selection of relevant scientific publications from the period of 2010–2025 was systematically analyzed using a Systematic Literature Review (SLR) approach were thematically analyzed to identify conceptual shifts, theoretical trends, practices, and implementation barriers. The findings reveal a paradigm transition from a technology-focused leadership to a strategic role emphasizing agility, data-driven innovation, and ethics. Modern digital leaders are no longer just technology managers but ecosystem orchestrators tasked with balancing technology, pedagogy, and equity to address infrastructural, capacity, and cultural challenges. Although theoretical frameworks like transformational and distributed leadership are widely used, longitudinal and comparative research remains limited. This review positions digital leadership as an adaptive, ethical, and systemic practice, proposing a future research agenda focused on theory integration, cultural diversification, human-centered ethics, and policy translation to build equitable and intelligent educational systems